Dissociation of TRIF bias and adjuvanticity. Issue 27 (2nd June 2020) - Richard, Katharina; Perkins, Darren J.; Harberts, Erin M.; Song, Yang; Gopalakrishnan, Archana; Shirey, Kari Ann; Lai, Wendy; Vlk, Alexandra; Mahurkar, Anup; Nallar, Shreeram; Hawkins, Lynn D.; Ernst, Robert K.; et al.
Graphical abstract: Highlights: Synthetic lipid A analog adjuvants, E6020 and sMPL, signal through TLR4/MD2. E6020 preferentially activates the TRIF-dependent TLR4 signaling pathway. E6020 interacts more strongly with TLR4/MD2 and is internalized more rapidly. Despite TRIF-bias, E6020 and sMPL exhibit comparable adjuvanticity in vivo . Conclusion: Our study shows that a "TRIF bias" is dissociable from adjuvanticity. Abstract: Toll-like receptors (TLRs), a family of "pattern recognition receptors, " bind microbial and host-derived molecules, leading to intracellular signaling and proinflammatory gene expression. TLR4 is unique in that ligand-mediated activation requires the co-receptor myeloid differentiation 2 (MD2) to initiate two signaling cascades: the MyD88-dependent pathway is initiated at the cell membrane, and elicits rapid MAP kinase and NF-κB activation, while the TIR-domain containing adaptor inducing interferon-β (TRIF)-dependent pathway is initiated from TLR4-containing endosomes and results in IRF3 activation. Previous studies associated inflammation with the MyD88 pathway and adjuvanticity with the TRIF pathway. Gram-negative lipopolysaccharide (LPS) is a potent TLR4 agonist, and structurally related molecules signal through TLR4 to differing extents. Herein, we compared monophosphoryl lipid A (sMPL) and E6020, two synthetic, non-toxic LPS lipid A analogs used as vaccine adjuvants, for their capacities to activate TLR4-mediated innate immune responses and to enhance antibody production. In mouse macrophages, high dose sMPL activates MyD88-dependent signaling equivalently to E6020, while E6020 exhibits significantly more activation of the TRIF pathway (a "TRIF bias") than sMPL. Eritoran, a TLR4/MD2 antagonist, competitively inhibited sMPL more strongly than E6020. Despite these differences, sMPL and E6020 adjuvants enhanced antibody responses to comparable extents, with balanced immunoglobulin (Ig) isotypes in two immunization models. These data indicate that a TRIF bias is not necessarily predictive of superior adjuvanticity.